Analisis Dan Perancangan Sistem Informasi Manajemen Evaluasi Kinerja Dosen Pada Universitas Batanghari - Syakurah, Syakurah; Siahaan, Kondar (Jurnal Manajemen Sistem Informasi, 2020)
Evaluation of the performance of lecturers at Batanghari University is carried out every semester bydistributing questionnaires in the form of sheets of paper given to students and permanent lecturers at theend of the semester exams. Problems that are constrained in the current system, namely the lack of staffdistribution of questionnaires, submission of questionnaire files that have been filled out by students andlecturers is slow, recapitulation of data using the Microsoft Excel program, submission of recapitulationof lecturer data is often late from the specified time limit, report preparation takes a long time, besidesthat there is also a pile up of questionnaire files. The purpose of this study was to analyze and design amanagement information system for evaluating the performance of lecturers at Batanghari University.Analysis of system requirements using UML (Unified Modeling Language) tools, namely usecasediagrams, activity diagrams, and class diagrams. This research resulted in a prototype design ofmanagement information system evaluating lecturer performance in the form of IKAD report andLecturer Satisfaction. The author hopes that the next stage of implementation can be used for the futureand can be a reference for other researchers discussing the same or similar topics.